Proyecto de inversión para la implementación de una sucursal de la empresa K-Centro Pica en la ciudad de Loja - Jacome Quezada, Ligia Estefania (2016)
When concluding the elaboration of the present thesis work, it is necessary to manifest the main results of the informed work and minutely carried out during the whole investigative process. This investigation has as general objective to carry out a "PROJECT OF INVESTMENT FOR THE IMPLEMENTATION OF A BRANCH OF THE COMPANY K-CENTER it ITCHES IN THE CITY DE LOJA" In the development of the investigation the use of Methods was needed and Technical that the investigation allows to carry out; among these we have the Deductive Method, the Inductive Method, the Statistical Method among other. The Descriptive Method is a process that allows to analyze descriptions of facts and current phenomena, the Deductive Method it is about the scientific most usual method that is characterized by 4 stages the observation and registration of all the facts: the analysis and the classification of the facts; the inductive derivation of a generalization starting from the facts and the contrastación, the Inductive Method is an analytic-synthetic process, by means of which leaves of the study of facts or particular phenomena, to arrive to the discovery of a principle or general law, the Analytic Method implies the synthesis this is the union of the elements to form an everything. Among the used investigation Techniques they are: the Direct Observation that is the orderly, conscious and systematic perception that he/she helped to know which the necessities of the clients are, their demands, preferences and likes; the Survey is a technique of gathering of information by means of written questions organized in a printed questionnaire. The use of all these methods allowed to arrive to the culmination of the present I project since to achieve it one had to apply the different studies for the understanding and demonstration of the same one In the Study of Market carried out in the City of of Loja, a sample of 398 families and 1 distributor authorized for the sale of articles of plastic to those that interview them to him, was determined he/she stops then to carry out the market analysis determining the Potential Demand of 51463 families, the Real Demand of 43743 families and the Effective Demand of 42868 families in the year 2015. The Offer of 12480 families assisted annually and the Unsatisfied Demand of 41768 families, which allowed to determine that if you can execute the project for the results obtained in the analysis of the demand, the offer and the levels of commercialization of the product. The Installed Capacity of the project determines that the company will be in capacity of assisting 12480 clients and used capacity will belong to 8736 clients of which will be of 70% for the first year, the localization of the same one it is also determined that will be located in the city of Loja in the Street November 18 and Cariamanga, In the engineering of the Project it is determined the characteristics of the operability, processes and technical requirements as the location of furniture tackle, facilities and teams. In the administrative study it is determined like a Company of Limited Responsibility and with an Organic Functional structure at the levels so much Hierarchical Legislative, Executive, Advisory Level, Auxiliary Level of Support, and Operative Level, as well as manuals of functions, flowcharts that served as rule to implement a good organization that will have the personal following Manager, Secretary-cashier, grocer and two salespersons. The project reaches an investment of $ 37.698,57 dollars that will be financed with a contribution of the partners of 52.25% of the total of the investment that corresponds to $ 19.698,57 and a loan that it will maintain the project with the National Bank of Development that constitutes 47.75% that corresponds to $ 18.000,00 dollars to 5 years term to 15% of annual interest. The financial evaluation presents the following results: According to VAN of the present project he/she gives us a positive value of $ 101.312,98 what indicates that the project if it is feasible for the investment. TIR is of 70.82% being this satisfactory value to carry out the project, with regard to the time to recover the investment will be in 1 year 4 months and 17 days, the values of the analysis of sensibility are smaller than 1 therefore it doesn't affect the project the changes in the increased costs and the revenues diminished in 16,5% and in a 13,% respectively; that is to say the project is not sensitive to these changes. Finally he/she thinks about the conclusions and more important recommendations of the project.